Review of Poematica del Principio Tai Chi, by Massimo Mori (Revista de Artes Marciales Asiáticas, 2021)
This review covers the book Poematica del Principio Tai Chi (Firenze, Italy, 2020) by Massimo Mori, that gather a lifetime multicultural researches converging on the Tai Chi, Supreme Principle coming from the unknowable Dao. When applied to the martial art, tai chi becomes taijiquan, “Punch of the Supreme Principle”. The first chapters provide the coordinates to deepen a holistic paradigm through different trajectories ranging from the classical cultures of the East and the West to the globalized contemporaneity. Complex and fascinating themes are creatively addressed in the subsequent chapters. The book ranges from theology to theoretical philosophy, from physics to literature and art, even to cinema. The chapters on I Qing and Daodejing indicate how the holistic vision of a conscious wisdom can be defined as systemic and essential in the relationship between culture and nature. If the Dao is the Way, this has to be followed in the name of a natural ethic that the Daodejing shows with an enlightening wisdom. Thus, the practice of Taijiquan becomes the “martial art of peace” and the Taiji Supreme Principle, practicable in every activity, is the paradigm of a renewed humanism. Massimo Mori is considered among the masters who have dedicated their existence to the wisdom vision of a New Horizon – as he called his school - and his book is a premise to imagine peace between East and West, between all the people of the globe living under the same sky.